Pengembangan E-Booklet Interaktif Keanekaragaman Ikan di TPI Tambaklorok Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMA - Resti Fitriati; Ari Yuniastuti; Nur Kusuma Dewi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to develop interactive e-booklets based on the local potential to improve learners' science process skills. This research method is Research & Development (R&D) with a 4D model consisting of 4 main stages, namely, define. Design, develop and disseminate. The product of this research is an interactive e-booklet. The subject of the study was a grade X student of Al Fattah Terboyo High School. The e-booklet was validated by media experts and material experts, each consisting of one lecturer and two teachers as experts. The results showed that interactive e-booklets are included in the category of very valid and worthy of use in learning, and interactive e-booklets are effective enough to improve the science process skills of learners, but science process skills still need to be trained again to learners.